2013
DOI: 10.1073/pnas.1314608110
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of somatic mutations and clonal evolution in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive tumor, but a subset of patients may follow an indolent clinical course. To understand the mechanisms underlying this biological heterogeneity, we performed whole-genome and/or whole-exome sequencing on 29 MCL cases and their respective matched normal DNA, as well as 6 MCL cell lines. Recurrently mutated genes were investigated by targeted sequencing in an independent cohort of 172 MCL patients. We identified 25 significantly mutated genes, including known drivers suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
361
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(390 citation statements)
references
References 43 publications
19
361
3
2
Order By: Relevance
“…This hotspot mutation has been recurrently reported in mantle cell lymphoma 35 and in pediatric BCP-ALL 36,37 and results in cellular transformation. 36 The emergence of a clone carrying the WHSC1 E1099K mutation may have been sufficient to induce early relapse in this patient.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 84%
“…This hotspot mutation has been recurrently reported in mantle cell lymphoma 35 and in pediatric BCP-ALL 36,37 and results in cellular transformation. 36 The emergence of a clone carrying the WHSC1 E1099K mutation may have been sufficient to induce early relapse in this patient.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 84%
“…3). BIRC3 inactivating mutations have been described in CLL, SMZL [91] and MCL [92,93], while TRAF3 mutations can be observed in CLL [4,10,11], SMZL [48, 94,95], DLBCL [96] and myeloma [97,98].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…Richard Rosenquist, 1 Andreas Rosenwald, 2 Ming-Qing Du, 3 Gianluca Gaidano, 4 Patricia Groenen, 5 Andrew Wotherspoon, 6 Paolo Ghia, 7 Philippe Gaulard, 8 Elias Campo, 9 Kostas Stamatopoulos, 10 on behalf of the European Research Initiative on CLL (ERIC) and the European Association for Haematopathology (EAHP) become possible to appreciate the panorama of recurrently affected genes that contribute to disease pathogenesis and/or evolution, at least in major lymphoma subtypes. Mounting evidence suggests that certain gene mutations have diagnostic, prognostic and/or predictive impact.…”
Section: Clinical Impact Of Recurrently Mutated Genes On Lymphoma Diamentioning
confidence: 99%
“…3 However, for the great majority of lymphomas, including chronic lymphocytic leukemia (CLL), 4 diffuse large B-cell lymphoma (DLBCL), 5 follicular lymphoma (FL), 6 mantle cell lymphoma (MCL), 7 Burkitt lymphoma (BL), 8 splenic marginal zone lymphoma (SMZL) 9 and most peripheral T-cell lymphoma (PTCL) subtypes, [10][11][12][13] NGS studies have revealed a quite diverse and complex mutation pattern, with a limited number of frequently mutated genes accompanied by a long tail of genes with low-frequency mutations. In addition, while some genes are biased to certain lymphoma entities, e.g.…”
Section: Clinical Impact Of Recurrently Mutated Genes On Lymphoma Diamentioning
confidence: 99%
See 1 more Smart Citation